Brief Report: Association Between Pregnancy Outcomes and Death From Cardiovascular Causes in Parous Women With Systemic Lupus Erythematosus: A Study Using Swedish Population Registries. Issue 9 (September 2015) - Soh, May Ching; Nelson‐Piercy, Catherine; Dib, Fadia; Westgren, Magnus; McCowan, Lesley; Pasupathy, Dharmintra
<x xml:space="preserve">Abstract</x> Objective To determine if maternal placental syndromes (MPS) are associated with an increased risk of death from cardiovascular causes in women with systemic lupus erythematosus (SLE). Methods Between 1973 and 2011, women with SLE and a history of pregnancy were identified using linked Swedish population registries. The outcome was death from primarily cardiovascular causes, defined as death from acute coronary syndrome or coronary artery disease, stroke, or peripheral vascular disease. The exposure was MPS, defined as any hypertensive disorders in pregnancy, stillbirth, placental abruption, or delivery of a small‐for‐gestational‐age infant. The association of preterm delivery (delivery at <34 weeks of gestation) with death from cardiovascular causes was also explored. Risk of death from cardiovascular causes was determined using logistic regression, adjusting for the year of first delivery, duration of SLE, number of inpatient admissions, and cardiovascular risk factors. Results A total of 3, 977 women with SLE had 7, 410 pregnancies during the study interval. Death from primarily cardiovascular causes occurred in 44 of the 325 women who died (13.5%). The median age at death from cardiovascular causes was 54 years (interquartile range 48–58 years), and these women were more likely to have had hypertension and renal disease. MPS was associated with an increased risk of death from primarily cardiovascular causes (adjusted odds ratio [OR] 2.19 [95% confidence interval (95% CI) 1.14–4.22]), specifically, a history of placental abruption (adjusted OR 5.78 [95% CI 1.61–20.72]). Delivery at <34 weeks of gestation, particularly when combined with MPS, was also associated with an increased risk of death from primarily cardiovascular causes (adjusted OR 2.49 [95% CI 1.06–5.85]). Conclusion MPS in pregnancy is associated with a higher risk of death from primarily cardiovascular causes in women with SLE.